GaN-Based DC-DC Resonant Boost Converter with Very High Efficiency and Voltage Gain Control - Zbigniew Waradzyn; Robert Stala; Andrzej Mondzik; Aleksander Skała; Adam Penczek (Energies, 2020)
This paper presents a concept for the operation of a resonant DC–DC switched-capacitor converter with very high efficiency and output voltage regulation. In its basic concept, such a converter operates as a switched-capacitor voltage doubler (SCVD) in the Zero Current Switching (ZCS) mode with a constant output voltage. The proposed methods of switching allow for the switched-capacitor (SC) converter output voltage regulation, and improve its efficiency by the operation with Zero Voltage Switching (ZVS). In this paper, various switching patterns are proposed to achieve high efficiency and the output voltage control by frequency or duty cycle regulation. Some examples of the application of the proposed switching patterns are presented: in current control at the start-up of the converter, in a bi-directional converter, and in a modular cascaded system. The paper also presents an analytical model as well as the relationships between the switching frequency, voltage ratio and efficiency. Further, it demonstrates the experimental verification of the waveforms, voltage ratios, as well as efficiency. The proposed experimental setup achieved a maximum efficiency of 99.228%. The implementation of the proposed switching patterns with the ZVS operation along with the GaN-based (Gallium Nitride) design, with a planar choke, leads to a high-efficiency and low-volume solution for the SCVD converter and is competitive with the switch-mode step-up converters.